Ligand‐Controlled Palladium‐Catalyzed Regiodivergent Defluorinative Allylation of gem‐Difluorocyclopropanes via σ‐Bond Activation. Issue 19 (26th July 2022) - Wu, Lei; Wang, Minyan; Liang, Yong; Shi, Zhuangzhi
Comprehensive Summary: Monofluoroalkenes are important and versatile privileged components in pharmacologically relevant molecules. Here, we report a method for the selective construction of these compounds in a diversity‐oriented fashion through regiodivergent cross‐coupling of gem ‐difluorocyclopropanes with allylboronates by employing a palladium catalyst with two different ligands, in which gem ‐difluorocyclopropanes were used as allyl electrophiles by C—C and C—F bond activation. In the presence of 2‐biphenylyl(diphenyl)phosphine as ligand, the linear‐selective allyl–allyl bond formation is highly obtained, while utilizing the sterically hindered BrettPhos (dicyclohexyl[3, 6‐dimethoxy‐2', 4', 6'‐tris(1‐methylethyl)[1, 1'‐biphenyl]‐2‐yl]phosphine) as the ligand favors the generation of the branched‐selective product. Experimental and computational studies investigated the key steps of the cross‐coupling reactions, revealing the origin of the ligand‐controlled regiodivergence. Abstract :